2015
DOI: 10.1002/poc.3520
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and kinetics of the oxidative damage to ergosterol induced by peroxyl radicals in lipid media: a theoretical quantum chemistry study

Abstract: In this work, we have studied the mechanisms and kinetics of the initial damage to ergosterol induced by• OOH and• OOCH 3 peroxyl radicals in a lipid media, using quantum chemistry and computational kinetics methods. The initial damage to ergosterol induced by these radicals occurs predominantly through the hydrogen transfer mechanism (HT) from the allylic position C14 of ergosterol. For the reaction of ergosterol with• OOH, the HT-9 pathway represents~90.8% of the overall rate constant, while in the case of• … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 62 publications
(61 reference statements)
1
16
0
1
Order By: Relevance
“…Yin et al suggested mechanisms involving abstraction of hydrogen atoms at either C‐9 or C‐14 of the sterol 24 . This was further confirmed for ergosterol with the C‐9 mechanism representing the highest contribution to ergosterol damage by peroxyl radicals 27 …”
Section: Resultssupporting
confidence: 94%
“…Yin et al suggested mechanisms involving abstraction of hydrogen atoms at either C‐9 or C‐14 of the sterol 24 . This was further confirmed for ergosterol with the C‐9 mechanism representing the highest contribution to ergosterol damage by peroxyl radicals 27 …”
Section: Resultssupporting
confidence: 94%
“…[48] However, β-sitosterol reacts with the • OOH radical slower than ergosterol (2.05 × 10 6 M −1 s −1 ). [49] Equally important, β-sitosterol also reacts with the peroxyl radical • OOH slightly faster than some known antioxidants, such as α-mangostin (7.8 × 10 3 M −1 s −1 ), [50] capsaicin (6.5 × 10 3 M −1 s −1 ), [51] and protocatechuic acid (5.1 × 10 3 M −1 s −1 ). [52]…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained on the radical scavenging activity from HMD with • OOH in lipid media could be employed to compare this activity with other antioxidants, according to this, the HMD is better antioxidant than tyrosol (7.13 × 10 2 M ‐1 s ‐1 ), capsaicin (6.54 × 10 3 M ‐1 s ‐1 ), sinapinic acid (1.66 × 10 4 M ‐1 s ‐1 ), fraxetin (2.43 × 10 4 M ‐1 s ‐1 ), esculetin (4.93 × 10 4 M ‐1 s ‐1 ), sesamol (3.33 × 10 4 M ‐1 s ‐1 ), trans‐Resveratrol (1.42 × 10 5 M ‐1 s ‐1 ), hydroxytyrosol (6.42 × 10 5 M ‐1 s ‐1 ), dopamine (8.16 × 10 5 M ‐1 s ‐1 ), canonol (6.80 × 10 5 M ‐1 s ‐1 ); since the HMD reacts lower than ergosterol (2.05 × 10 6 M ‐1 s ‐1 ) in lipid media.…”
Section: Resultsmentioning
confidence: 99%